Global Economic Prospects 2009 : Commodities at the Crossroads - World Bank (World Bank, 2012)
The release of this year's global economic prospects finds the world economy at a crossroads. Markets all over the world are engulfed in a global economic crisis, with stock markets sharply down and volatile, almost all currencies having depreciated substantially against the dollar, and risk premiums on a wide range of debt having increased by 600 or more basis points. Commodity markets too have turned a corner. Following several years of increase, prices have plummeted, and although well above their 1990s levels, they have given up most of the increases of the past 24 months. Chapter one of this report examines the medium-term implications of this crisis for developing-country growth, inflation, and world trade. Chapter two looks at longer-term supply and demand prospects in commodity markets. It takes into account the long-term growth prospects of developing countries and their rising share in world GDP (gross domestic product), the declining quality of new pools of resources, and the influence of technology on both demand and supply. Finally, chapter three reports on the poverty impacts of high commodity prices and examines the effectiveness of policies in both producing and consuming countries in dealing with the challenges posed by periodic bouts of high commodity prices.